การเสียวฟันหลังการบูรณะด้วยวัสดุบูรณะฟันเรซินคอมโพสิต - ลีลาพงศ์ฤทธิ์ ศีลัสยา; กระจ่างตา นันทวรรณ; คล้ายศิริ อวิรุทธ์ (Srinakharinwirot University Dental Journal (E-ISSN 2774-0811), 2021)
บทคัดย่อ บทความปริทัศน์นี้มีวัตถุประสงค์เพื่อรวบรวมสาเหตุของการเกิดอาการเสียวฟันหลังบูรณะด้วยวัสดุเรซินคอมโพสิตซึ่งมักพบได้มาก โดยจะอธิบายถึงสาเหตุ การแก้ไข และการป้องกันไม่ให้เกิดอาการเสียวฟัน หลังจากบูรณะด้วยวัสดุชนิดนี้ ทันตแพทย์ผู้ทำการบูรณะควรศึกษาถึงคุณสมบัติ และเทคนิคขั้นตอนการบูรณะอย่างละเอียด เพื่อป้องกันปัญหาการเสียวฟันที่อาจจะเกิดขึ้นได้ คำสำคัญ: สารยึดติด เรซินคอมโพสิต ภาวะเสียวฟัน Post-Operative Sensitivity in Resin Composite Restoration Seelasaya Leelaponglit Nantawan Krajangta Awiruth Klaisiri Abstract This study is a review of published papers on post-operative sensitivity causing resin compositerestoration. The review article provides the causes, solutions and prevention of this complication,which will be useful for dentists to achieve a successful restorative treatment. The properties andproper restorative techniques is necessary for prevention any possible symptoms in the treatment. Keywords: Adhesive, Resin composite, Tooth sensitivity ว.ทันต.มศว ปีที่ 14 ฉบับที่ 1 พ.ศ. 2564 หน้า 81-90. SWU Dent J. 2021;14(1):81-90.